Odpowiedź:
Założenia: [tex]x\neq 3 \wedge x\neq -2[/tex]
[tex]\frac{2}{x-3}+\frac{4 x}{x+2}=1-\frac{2}{3}=\frac{1}{3}[/tex]
[tex]\frac{2(x+2)+4x(x-3)}{(x-3)(x-2)} = \frac{1}{3}[/tex]
[tex]\frac{2x+4+4x^2-12x}{(x-3)(x-2)} = \frac{1}{3}[/tex]
[tex]\frac{4x^2-10x+4}{(x-3)(x-2)} = \frac{1}{3}[/tex]
[tex]\frac{2(2x^2-5x+2)}{(x-3)(x-2)} = \frac{1}{3}[/tex]
[tex]6\left(2 x^2-5 x+2\right)=(x-3) (x+2)[/tex]
[tex]12x^2-30 x+12=x^2-x-6[/tex]
[tex]11 ^2-29 x+18=0[/tex]
[tex](x-1)(11x-18)=0[/tex]
[tex]x=1 \vee 11x=18[/tex]
[tex]x=1 \vee x=\frac{18}{11}[/tex]
Założenia spełnione dla rozwiązań.